2010
DOI: 10.1002/ieam.139
|View full text |Cite
|
Sign up to set email alerts
|

Chemical activity as an integrating concept in environmental assessment and management of contaminants

Abstract: It is suggested that chemical activity in environmental media can serve as an integrating concept for holistic evaluations of contaminants, including their fate and effects. In support of this assertion, information underlying the thermodynamic principles and the relationships between monitored and modeled concentrations and activities are presented. The toxicological significance of activity is discussed, with emphasis on substances that exert baseline narcosis. Illustrations are given of the application of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…Chemical activity (a, unitless) is closely related to the lipidbased critical body residue as activity in the lipid phase is a product of the chemical's mole fraction in the lipid and the activity coefficient in that phase [1]. The activity coefficients of nonpolar narcotics in octanol (often an assumed surrogate for organic phase toxicity target sites) are relatively constant [15,16]. Chemical activity is directly related to concentration.…”
Section: Alternative Dose Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical activity (a, unitless) is closely related to the lipidbased critical body residue as activity in the lipid phase is a product of the chemical's mole fraction in the lipid and the activity coefficient in that phase [1]. The activity coefficients of nonpolar narcotics in octanol (often an assumed surrogate for organic phase toxicity target sites) are relatively constant [15,16]. Chemical activity is directly related to concentration.…”
Section: Alternative Dose Metricsmentioning
confidence: 99%
“…Further analysis indicated that critical body residues associated with acutely lethal baseline neutral narcosis in small aquatic organisms typically range between approximately 2 mmol/kg and 8 mmol/kg (wet wt, $5% body lipid) and that different critical body residue ranges could be associated with standard fish mode of toxic action categories from narcosis to tetrachlorodibenzo-p-dioxin-like toxicity for both acute (lethal) and chronic responses [12,13]. Percentage of volume fractions in organism lipid phases and chemical activity have also been discussed as possible metrics for baseline narcosis toxicity and risk assessment [10,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been proposed and experimentally conrmed that chemical activity is a key parameter for the baseline toxicity of hydrophobic organic chemicals, and that some highly hydrophobic substances can exert baseline toxicity at low aqueous concentrations but at relatively high chemical activities. [9][10][11][12][13][14][15] These, and other studies, suggest that exposure to hydrophobic organic substances is better described by freely dissolved concentrations and chemical activity than the total chemical concentration, since partitioning and diffusive uptake are spontaneous processes that are driven by differences in chemical activity. Because they can accumulate in sediments, PAHs have oen been examined in this environmental compartment, in relation to their role in exposure and their effects on aquatic life.…”
Section: Introductionmentioning
confidence: 89%
“…The approach of using baseline narcosis and relative toxicity ratios has been suggested when graphically comparing multimedia monitored and model-estimated concentrations as fugacities or activities [35,36]. The use of fugacity or activity (which is simply fugacity divided by liquid state vapor pressure) tends to consolidate multimedia levels into a narrower band.…”
Section: Future Prospects and Conclusionmentioning
confidence: 99%